Cover Picture: Reversible Mechanical Switching of Magnetic Interactions in a Molecular Shuttle (ChemistryOpen 1/2015). Issue 1 (February 2015) - Bleve, Valentina; Schäfer, Christian; Franchi, Paola; Silvi, Serena; Mezzina, Elisabetta; Credi, Alberto; Lucarini, Marco
<x xml:space="preserve">Abstract</x> The cover picture shows coupled and uncoupled states of a [2]rotaxane incorporating stable nitroxide radical units in both the ring and dumbbell components. Interaction between nitroxide radicals could be switched between noncoupled (three‐line electron paramagnetic resonance (EPR) spectrum) and coupled (five‐line EPR spectrum) upon deprotonation of the rotaxane NH2+ centers that effects a quantitative displacement of a dibenzocrown macroring to a 4, 4′‐bipyridinium recognition site. The complete base‐ and acid‐induced switching cycle of the EPR pattern was repeated several times without an appreciable loss of signal, highlighting the reversibility of the process. Hence, this molecular machine is capable of switching on/off magnetic interactions by chemically driven reversible mechanical effects. For more details, see the Communication on 10.1002/open.201402073 ((p. 18 ff.))<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>